(untitled) (Research, Society and Development, 2021)
The meaning of the word delirium is attributed to the Latin “delirare”, which means “to be out of place.” On the articles included in this review, it was observed that there was a prevalence of studies published in the years of 2016 and 2020. As a result, after significant content analysis, he obtained the following predisposing factors: age equal to or greater than 60 years, the use of sedoanalgesics, invasive mechanical ventilation, physical restriction, dehydration and malnutrition, typical ICU environment and sleep disturbance. Given this study, we can say that delirium is a very common problem in patients admitted to the ICU. The first step to intervene in this situation is to prevent, creating delirium prevention protocols based on risk factors in order to call professionals’ attention to patients who have a positive result for these factors. should be considered an emergency in the ICU, and educate professionals about it it is of utmost importance, so that they remain under constant neurological surveillance so that they can act assertively in the diagnosis and treatment of the same.